The Role of Interdisciplinary Approaches in Developing Visual Literacy in Students - Kamolova E’zoza Iskandar qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article investigates the significance of interdisciplinary approaches in visual arts education for developing students’ visual literacy. Drawing on research by Shovdirov S. A. and Ibraimov X., the study highlights strategies that integrate knowledge from multiple fields such as history, mathematics, biology, and cultural studies to enhance creative and cognitive competencies. It emphasizes how interdisciplinary teaching methods, combined with project-based and interactive learning, improve students’ analytical, creative, and reflective skills, preparing them for contemporary academic and professional challenges.